2009
DOI: 10.1111/j.1365-2109.2009.02444.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a microsatellite multiplex genotyping tool for the fish Gilthead seabream (Sparus aurata): applicability in population genetics and pedigree analysis

Abstract: In spite of the numerous studies performed in the aquacultured ¢sh gilthead seabream, the overall structure of wild and cultivated stocks is rather confusing. In this study, we developed a10 microsatellite genotyping tool SaGT(614), conformed by two polymerase chain reaction-multiplex reactions (SaGT6 and SaGT4), which can be simultaneously combined in automatic sequencers. The utility of this tool was proven through the following applications: (i) characterization and differentiation of wild and cultivated po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 31 publications
6
22
0
Order By: Relevance
“…A similar situation was observed in the parental assignment of male cod breeders to progeny (Bekkevold et al, 2002) and this coupled with observations of cod reproductive behaviour (Brawn, 1961;Hutchings et al, 1999) suggested that cod males had reproductive hierarchies that explained the dominance of progeny by certain males (Bekkevold et al, 2002). A similar coupling of the present study on gilthead seabream spawning behaviour with studies on parental assignment of gilthead seabream progeny (Brown et al, 2005;Porta et al, 2009;Chavanne et al, 2012) also suggested the hypothesis that gilthead seabream had reproductive hierarchies that resulted in the dominance of progeny by certain breeders particularly amongst males. Chavanne et al (2012) concluded that further research was required to understand the spawning kinetics of gilthead seabream.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…A similar situation was observed in the parental assignment of male cod breeders to progeny (Bekkevold et al, 2002) and this coupled with observations of cod reproductive behaviour (Brawn, 1961;Hutchings et al, 1999) suggested that cod males had reproductive hierarchies that explained the dominance of progeny by certain males (Bekkevold et al, 2002). A similar coupling of the present study on gilthead seabream spawning behaviour with studies on parental assignment of gilthead seabream progeny (Brown et al, 2005;Porta et al, 2009;Chavanne et al, 2012) also suggested the hypothesis that gilthead seabream had reproductive hierarchies that resulted in the dominance of progeny by certain breeders particularly amongst males. Chavanne et al (2012) concluded that further research was required to understand the spawning kinetics of gilthead seabream.…”
Section: Discussionsupporting
confidence: 63%
“…Parental assignment of progeny also identified that the participation of gilthead seabream breeders was variable with a proportion of breeders that did not participate in spawning (Brown et al, 2005;Porta et al, 2009;Chavanne et al, 2012) and this variation or dominance by certain fish was particularly clear amongst male breeders (Brown et al, 2005). A similar situation was observed in the parental assignment of male cod breeders to progeny (Bekkevold et al, 2002) and this coupled with observations of cod reproductive behaviour (Brawn, 1961;Hutchings et al, 1999) suggested that cod males had reproductive hierarchies that explained the dominance of progeny by certain males (Bekkevold et al, 2002).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations